Prospective evaluation of indirect costs due to acute rotavirus gastroenteritis in Spain: the ROTACOST study - Sánchez-Lastres Juan; Redondo-Collazo Lorenzo; Bouzón-Alejandro Marta; Martinón-Torres Nazareth; Martinón-Sánchez José; Martinón-Torres Federico (BMC, 2011)
Abstract Background The effect of rotavirus in developed countries is mainly economic. This study aimed to assess the indirect costs induced by rotavirus acute gastroenteritis (RVAGE) in Spain. Methods A prospective observational study was conducted from October 2008 to June 2009. It included 682 children up to 5 years of age with acute gastroenteritis (AGE) who attended primary care (n = 18) and emergency room/hospital settings (n = 10), covering the regions of Galicia and Asturias (North-west Spain). All non-medical expenses incurred throughout the episode were recorded in detail using personal interviews and telephone contact. Results Among the 682 enrolled children, 207 (30.4%) were rotavirus positive and 170 (25%) had received at least one dose of rotavirus vaccine. The mean (standard deviation) indirect cost caused by an episode of AGE was estimated at 135.17 (182.70) Euros. Costs were 1.74-fold higher when AGE was caused by rotavirus compared with other etiologies: 192.7 (219.8) Euros vs. 111.6 (163.5) Euros (p < .001). The costs for absenteeism were the most substantial with a mean of 91.41 (134.76) Euros per family, resulting in a loss of 2.45 (3.17) days of work. In RVAGE patients, the absenteeism cost was 120.4 (154) Euros compared with 75.8 (123) for the other etiologies (p = .002), because of loss of 3.5 (3.6) vs 1.9 (2.9) days of work (p < .001). Meals costs were 2-fold-higher (48.5 (55) vs 24.3 (46) Euros, p < .001) and travel costs were 2.6-fold-higher (32 (92) vs 12.5 (21.1) Euros, p = .005) in RVAGE patients compared with those with other etiologies. There were no differences between RVAGE and other etiologies groups regarding costs of hiring of caregivers or purchase of material. Patients with RVAGE were admitted to hospital more frequently than those with other etiologies (47.8% vs 14%, p < .001). Conclusions Rotavirus generates a significant indirect economic burden. Our data should be considered in the decision-making process of the eventual inclusion of rotavirus vaccine in the national immunization schedule of well developed countries.